Biofabrication of brain-like living tissue: structure to intelligence - Ling Wang; Sen Wang; Yingjie Liu; Bowen Zhang; Zhaoyu Pan; Luge Bai; Siqi Yao; Chenrui Zhang; Huangfan Xie; Jiankang He; Dichen Li (International Journal of Extreme Manufacturing)
Brain, the material foundation of human intelligence, is the most complex tissue in the human body. Brain diseases are among the leading threats to human life, yet our understanding of their pathogenic mechanisms and drug development remains limited, largely due to the lack of accurate brain-like tissue models that replicate its complex structure and functions. Therefore, constructing brain-like models—both in morphology and function—possesses significant scientific value for advancing brain science and pathological pharmacology research, representing the frontiers in the biomanufacturing field. This review outlines the primary requirements and challenges in biomanufacturing brain-like tissue, addressing its complex structures, functions, and environments. Also, the existing biomanufacturing technologies, strategies, and characteristics for brain-like models are depicted, and cutting-edge developments in biomanufacturing central neural repair prosthetics, brain development models, brain disease models, and brain-inspired biocomputing models are systematically reviewed. Finally, the paper concludes with future perspectives on the biomanufacturing of brain-like tissue transitioning from structural manufacturing to intelligent functioning.